2009
DOI: 10.1590/s2236-89062009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia comparada do lenho de Piptadenia gonoacantha (Mart.) J.F.Macbr. em dois tipos de vegetação

Abstract: -(Comparative wood anatomy of Piptadenia gonoacantha (Mart.) J.F.Macbr. in two vegetation types). Ecological anatomy aims to correlate the morphological and anatomical structures of plants with climatic, geographic and soil data. This study evaluated the qualitative and quantitative differences in the "pau-jacaré" wood -Piptadenia gonoacantha trees from Cantareira State Park (PEC) and Caetetus Ecological Station (EEC), respectively areas of Dense Ombrophylous Forest (Atlantic Forest) and Semi-deciduous Seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
3
0
1
Order By: Relevance
“…Hayden et al (2010) studied P. constricta submitted to different irrigation conditions in western Mexico and detected no effect on annual tree-ring formation, even with dry-season precipitation. The anatomical features observed in the individuals analyzed in our study corresponded to previous descriptions (Evans et al 2006;Lisi et al 2008;Longui et al 2009). The observed results indicate potential for developing dendrochronological and dendroecological research in the Ombrophilous Dense Forest using this species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hayden et al (2010) studied P. constricta submitted to different irrigation conditions in western Mexico and detected no effect on annual tree-ring formation, even with dry-season precipitation. The anatomical features observed in the individuals analyzed in our study corresponded to previous descriptions (Evans et al 2006;Lisi et al 2008;Longui et al 2009). The observed results indicate potential for developing dendrochronological and dendroecological research in the Ombrophilous Dense Forest using this species.…”
Section: Discussionsupporting
confidence: 89%
“…This species has distinct tree rings marked by semiring porous, thick-walled and radially flattened fibers on latewood (fibrous zone) and marginal parenchyma (Evans et al 2006;Lisi et al 2008;Longui et al 2009), indicating its potential for dendrochronological research. However, dendrochronological investigation requires prior evaluation of the frequency of tree ring formation.…”
Section: Introductionmentioning
confidence: 99%
“…The lower frequency occurred in the CSP. In contrast, Longui et al (2009a) found a higher vessel frequency in the CSP in Piptadenia gonoacantha (Mart.) J.F.…”
Section: Discussionmentioning
confidence: 73%
“…This index refl ects that wood of CES and CSP is more effi cient in transport to water, but more vulnerable to embolism in relation to the other three areas. Longui et al (2009a), in Piptadenia gonoacantha (Mart.) J.F.Macbr., noted higher vulnerability index at CES with respect to the CSP.…”
Section: Discussionmentioning
confidence: 99%
“…As células do parênquima radial são exclusivamente procumbentes (Figura 1C). Longui et al (2009) encontraram valores médios de diâmetro dos vasos igual a 139,4 e 143,9 µm, para a madeira de P. gonoacantha, em dois locais distintos e frequência de 9 e 7 vasos mm -2 , sendo semelhante as características anatômicas observadas nesse trabalho.…”
Section: Caracterização Anatômicaunclassified